2019
DOI: 10.20533/jitll.2633.7681.2019.0015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Self-Organized Learning Environments (SOLEs) on EFL students in a college in Oman

Abstract: This paper is part of a larger project where the researchers explored English as a Foreign Language (EFL) students' experiences in learning English using Self-Organized Learning Environments (SOLEs) within the context of their English foundation year in a college setting in Oman. The purpose that guided this current paper is to investigate whether SOLE pedagogy is able to positively influence Omani EFL college students' learning beliefs and behaviours. Using a participatory action research design, data sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Penelitian di bidang pembelajaran yang menekankan tentang pentingnya implementasi pembelajaran aktif di perguruan tinggi, menunjukkan adanya hubungan antara lingkungan belajar aktif, partisipasi mahasiswa, motivasi belajar, dan tingkat kedalaman pengalaman belajar yang dilakukan oleh mahasiswa. Lingkungan belajar yang diorganisasi sendiri oleh mahasiswa (Self-Organized Learning Environments) dapat menjadi pendekatan pedagogik yang efektif dengan meningkatkan kemandirian dan memotivasi mahasiswa untuk mengkonstruksi pengetahuannya (Al Zakwani & Walker-Gleaves, 2019).…”
Section: A Pendahuluanunclassified
“…Penelitian di bidang pembelajaran yang menekankan tentang pentingnya implementasi pembelajaran aktif di perguruan tinggi, menunjukkan adanya hubungan antara lingkungan belajar aktif, partisipasi mahasiswa, motivasi belajar, dan tingkat kedalaman pengalaman belajar yang dilakukan oleh mahasiswa. Lingkungan belajar yang diorganisasi sendiri oleh mahasiswa (Self-Organized Learning Environments) dapat menjadi pendekatan pedagogik yang efektif dengan meningkatkan kemandirian dan memotivasi mahasiswa untuk mengkonstruksi pengetahuannya (Al Zakwani & Walker-Gleaves, 2019).…”
Section: A Pendahuluanunclassified
“…However, secondary school science education studies, in Southern Africa, have paid little attention to pedagogy that can improve the teaching and learning of "S" in STEM; instead they focus on the factors that lead to poor performance. (Al Zakwani & Walker-Gleaves, 2019;Heslup, 2018). For example, after studying the literature based on the SOLEs pedagogy, Heslup (2018) found that of the few studies that have been conducted using SOLEs pedagogy, almost all of them were based on English second language learning.…”
Section: Self-organized Learning Environments Pedagogymentioning
confidence: 99%
“…Heslup's (2018) finding is in line with Al Zakwani and Walker-Gleaves (2019), who found that SOLEs pedagogy improved post-secondary school students' learning autonomy and boosted their motivation to learn English. It was further asserted that SOLEs pedagogy is a poorly researched pedagogy (Al Zakwani & Walker-Gleaves, 2019). It can be argued that SOLEs pedagogy provides learner autonomy, and the implementation of SOLEs pedagogy motivates learners to engage in deep learning.…”
Section: Self-organized Learning Environments Pedagogymentioning
confidence: 99%
See 2 more Smart Citations